Deciphering the expression patterns of homologous recombination-related lncRNAs identifies new molecular subtypes and emerging therapeutic opportunities in epithelial ovarian cancer - Hua, Tian; Zhang, Xiao-Chong; Wang, Wei; Tian, Yun-Jie; Chen, Shu-Bo (Frontiers in Genetics, 2022)
Epithelial ovarian cancer (EOC) is the leading killer among women with gynecologic malignancies. Homologous recombination deficiency (HRD) has attracted increasing attention due to the significant implication in prediction of prognosis and response to treatments. Besides the germline and somatic mutations of homologous recombination (HR) repair genes, to widely and deeply understand the molecular characteristics of HRD, we sought to screen the long non-coding RNAs (lncRNAs) with regard to HR repair genes and to establish a prognostic risk model for EOC. Herein, we retrieved the transcriptome data from the Genotype-Tissue Expression Project (GTEx) and the Cancer Genome Atlas (TCGA). HR-related lncRNA (HRRlncRNA) associated with prognostic were identified by co-expression and univariate Cox regression analyses. The least absolute shrinkage and selection operator (LASSO) and multivariate stepwise Cox regression were performed to construct a HRRlncRNAs risk model containing AC138904.1, AP001001.1, AL603832.1, AC138932.1 and AC040169.1. Next, Kaplan-Meier analysis, time-dependent receiver operating characteristics (ROC), nomogram, calibration, and DCA curves were made to verify and evaluate the model. Gene set enrichment analyses (GSEA), immune analysis, and prediction of the half-maximal inhibitory concentration (IC50) in risk groups were also analyzed. The calibration plots showed a good concordance with the prognosis prediction. ROCs of 1-, 3-, and 5-year survival confirmed the well-predictive efficacy of this model in EOC. The risk score was used to divide patients into high-risk and low-risk subgroups. The low-risk group patients tended to exhibit a lower immune infiltration status, a higher HRD score. Further, consensus clustering analysis was employed to divide patients with EOC into three clusters based on expression of the five HRRlncRNAs, which exhibited significant difference of checkpoints expression levels and tumor microenvironment (TME) status. Taken together, the results of this project supported that the five HRRlncRNAs model might function as biomarker and prognostic indicator with respect to a predicting for PARP inhibitor and immune treatment in EOC.